Burdens of ANH outweigh benefits in the minimally conscious state - Glannon, Walter (Journal of medical ethics, 2013)
In the case of the minimally conscious patient M, the English Court of Protection ruled that it would be unlawful to withdraw artificial nutrition and hydration (ANH) from her. The Court reasoned that the sanctity of life was the determining factor and that it would not be in M's best interests for ANH to be withdrawn. This paper argues that the Court's reasoning is flawed and that continued ANH was not in this patient's best interests and thus should have been withdrawn.